2020
DOI: 10.1177/0363199020945215
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Marriages in Late Nineteenth to Early Twentieth Century: Comparing Russia and Norway

Abstract: This article compares interethnic and interreligious marriages in Russia and Norway during the decades around 1900. State churches dominated religious life in both countries with over 90 percent of the population but both were losing influence during the period we focus on—rapidly in Russia after the 1917 Revolution. The part on Norway employs nominative and aggregate census material which from 1865 asked questions about religious affiliation, while the Russian case study utilizes the database of church microd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…On the contribution of religious practices toward low death registration, the current study shows that mixed marriages in families undermined death registration due to religious conflicts. This is consistent with the findings in a study conducted in Norway in which religious intolerance was observed in the 19 th and twentieth centuries [ 22 ]. Religious fanatics could not associate with the dead who had converted from their traditional religions including registering such deaths.…”
Section: Discussionsupporting
confidence: 93%
“…On the contribution of religious practices toward low death registration, the current study shows that mixed marriages in families undermined death registration due to religious conflicts. This is consistent with the findings in a study conducted in Norway in which religious intolerance was observed in the 19 th and twentieth centuries [ 22 ]. Religious fanatics could not associate with the dead who had converted from their traditional religions including registering such deaths.…”
Section: Discussionsupporting
confidence: 93%
“…Orthodox: The Alliance of Church and Tradition Tested by Economy, Demography, and Ecology While Upper Don Orthodox perpetuated early marriage (brides aged [17][18], conceding over the years a slight upward trend, urban Orthodox adopted a slightly later marriage (20 years until 1889, 22 years after) and Lower Don Orthodox (19 years until 1889, 20 years after) fell between these two models. Figures 2 to 5 showed that all Orthodox groups are distinct from other denominational groups, even (rural) Buddhists and rural Old Believers, who might have been thought to be close by virtue of their rurality and their participation in the irregular army as Cossacks.…”
Section: Discussionmentioning
confidence: 99%
“…16 Most lived as self-governing communities. The case of the Don Army Territory is not exceptional: In the governorate of Ekaterinburg around 1900, Glavatskaya et al 17 on individual data also found few religious intermarriages. The largest denominational group remained the Orthodox (90% of the Don Army Territory's population), especially in the countryside.…”
Section: Context and Datamentioning
confidence: 99%